KEANEKARAGAMAN TUMBUHAN DIKOTIL DI KAMPUS UNIVERSITAS NEGERI PADANG - Melani Domisofa; Moralita Chatri (Jurnal Biogenerasi, 2026)
This study was motivated by the important role of campus green spaces in supporting plant biodiversity conservation. The aim of this research was to identify and describe the diversity of dicotyledonous plants on the campus of Universitas Negeri Padang, West Sumatra, Indonesia. The research was conducted from November to December 2025 using a descriptive method. Data were collected through direct field observations by recording morphological characteristics of dicotyledonous plants, including growth habit, stems, leaves, and flowers. Plant identification was supported by the PlantNet application and relevant botanical literature. The data were analyzed descriptively by classifying species based on taxonomic levels. The results showed that all recorded plants belonged to the dicotyledonous group within the class Magnoliopsida, comprising 25 species, 22 genera, 14 families, and 10 orders. Dominant families included Anacardiaceae, Myrtaceae, Euphorbiaceae, Rubiaceae, Apocynaceae, Solanaceae, and Combretaceae, which exhibit diverse ecological roles and benefits. In conclusion, the Universitas Negeri Padang campus supports a relatively high diversity of dicotyledonous plants and functions as an important habitat for plant biodiversity. This study is recommended as baseline data for green space management, further botanical research, and biology education.